Recent Status of Laparoscopic Distal Gastrectomy in Korea: A Multicenter Retrospective Cohort Study (Pre-study Survey of KLASS-07 Trial) - Choi, Chang In; Lee, Chang Min; Park, Ji Ho; Jee, Ye Seob; Lee, Han Hong; Jeong, Oh; Park, Sungsoo (Frontiers in Oncology, 2019)
Purpose: To analyze the surgical trend and brief postoperative results of laparoscopic distal gastrectomy (LDG) in Korea on the basis of a multicenter cohort. Materials and Methods: Data of 812 patients who underwent LDG between January and December 2016 were collected from 14 surgeons at 7 institutions. Patients were divided into laparoscopy-assisted distal gastrectomy (LADG) group and totally laparoscopic distal gastrectomy (TLDG) group. Perioperative and clinicopathologic outcomes were compared retrospectively. Results: Among the patients (n=222 (27.3%) LADG; n=590 (72.7%) TLDG), there are no significant differences in patient’s demographics (sex, age, body mass index, and American Society of Anesthesiologists score). Billroth-I anastomosis (84.7%) was most performed in the LADG group, but Billroth-II anastomosis (59.0%) in the TLDG group (p<0.001). The mean operative time was longer in the TLDG group (197.3±44.4 min vs. 222.0±60.2 min, p<0.001), and there was no statistical difference in the hospital stay between the two groups (9.6±4.8 days vs. 8.9±7.1 days, p=0.149). There were no significant differences in morbidity and mortality between the two groups. The length of proximal margin was longer in the TLDG group (4.3±3.1 cm vs. 6.0±3.4cm, p<0.001), but the distal margin was longer in the LADG group (6.5±3.7 cm vs. 5.5±3.1 cm, p<0.001). The distribution of operations among each institution was shown very heterogeneously Conclusion: There was no significant difference related to surgical outcome between LADG and TLDG in the pre-study survey prior to KLASS-07 trial. Therefore, to obtain more reliable data, well designed prospective randomized controlled study is needed.